Diagnostic value of the confocal laser scanning microscopy in vivo - A. A. Kubanova; A. A. Kubanov; V. A. Smolyannikova; N. V. Gribanov; YU. B. Makhakova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The confocal laser scanning microscopy in vivo is a promising study method to visualize cell structures of epidermis and papillary dermis without affecting the skin integrity, which provides for a resolution and contrast similar to those characteristic of the classical histology examination. Goal. To assess the confocal laser scanning microscopy in vivo (CLSM) technique for diagnosing actinic keratosis, psoriasis vulgaris and rosacea vs. the classical histology examination. Study materials. The article describes the results obtained by using the confocal laser scanning microscopy in vivo technique vs. the histology examination in 10 patients with erythematous actinic keratosis, 10 patients with extensive psoriasis and 10 patients with erythematous and papulous rosacea. Results. The article describes diagnostically significant signs of the diseases detected by using the confocal laser scanning microscopy in vivo as well as the potential of this method in terms of diagnosing inflammatory skin diseases.